Analisis Strategi dan Inovasi Pembelajaran pada Siswa Kelas Tinggi Sekolah Dasar Berdasarkan Studi Literatur Tahun 2022–2026 - Madina; Makmun; Tri Wahyuningsih; Taufik Hidayat (Jurnal Ragam Pengabdian, 2026)
The rapid advancement of educational technology and the implementation of the Merdeka Curriculum require teachers to apply innovative and student-centered learning strategies, especially for upper elementary school students. This study aims to analyze learning strategies and innovations implemented in upper elementary education based on literature published from 2022 to 2026. This study employed a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were obtained from articles indexed in Google Scholar, Garuda, Sinta, and DOAJ. Ten selected articles were analyzed through a narrative synthesis approach. The findings indicated that the most widely applied strategies included Problem Based Learning (PBL), Project Based Learning (PjBL), Inquiry Learning, Cooperative Learning, Differentiated Learning, and Deep Learning. Learning innovations involved the use of digital media, instructional videos, educational games, and interactive multimedia. These strategies positively influenced students’ learning outcomes, motivation, critical thinking, creativity, communication, and collaboration skills. Their successful implementation was supported by teacher competence, adequate learning resources, school support, and effective technology integration. However, infrastructure limitations, low digital literacy, and time constraints remained significant challenges. Overall, innovative and active learning strategies play an important role in improving the quality of learning in upper elementary schools.